Effect of Rice Bran Protein Extract on Enzymatic Browning Inhibition in Vegetable and Fruit Puree - Kubglomsong , Supatcha; Theerakulkait, Chockchai (Agriculture and Natural Resources, 2014)
The effect of rice bran protein extract (RBPE) on enzymatic browning inhibition in vegetable and fruit puree was investigated. Protein from defatted rice bran was prepared by alkaline extraction and isoelectric point precipitation. RBPE was prepared by dispersing rice bran protein precipitate in distilled water (DW) at 0.8% protein (weight per volume). Potato, banana or apple was blended with RBPE and their color values (L*, a* and b*) were measured. Polyphenol oxidase (PPO) inhibition was studied by measuring absorbance at 420 nm with catechol as the substrate. It was found that the browning values in potato, banana and apple puree treated with RBPE were lower than those treated with DW (P ≤ 0.05). The L* values and hue angles in potato, banana and apple puree treated with RBPE were higher than those treated with DW (P ≤ 0.05). RBPE showed the highest percentage browning inhibition in potato puree, followed by apple and banana puree, respectively (P ≤ 0.05). Moreover, RBPE had a higher percentage of PPO inhibition in potato than apple and banana, respectively (P ≤ 0.05). Therefore, RBPE could inhibit enzymatic browning in vegetable and fruit puree, especially potato puree.